The Effectiveness of the Teams Games Tournament (TGT) Cooperative Learning Model in Improving Students' Understanding of Social Studies Concepts - Nurlailatul Badriyah; Tetep; Lili Dianah (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2026)
This study aims to examine the implementation of the Teams Games Tournament (TGT) cooperative learning model in enhancing students’ understanding of Social Studies concepts among seventh-grade students at SMPN 3 Tarogong Kidul. The study is motivated by the low level of students’ conceptual understanding, which is influenced by teacher-centered instruction and limited student participation in the learning process. This research employed a qualitative approach using a descriptive method. The participants included a Social Studies teacher and seventh-grade students selected purposively. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the TGT model improves students’ engagement, learning motivation, and social interaction. In addition, students’ conceptual understanding increased, as indicated by their improved ability to explain, connect, and apply concepts effectively. Supporting factors include high student enthusiasm and effective group collaboration, while inhibiting factors involve low self-confidence and limited instructional time. Therefore, the TGT model can be considered an effective, interactive, and meaningful alternative strategy for Social Studies learning.